Eligibility of Thematic Student Worksheets Based Ethnoscience on Single Substance and Mixed Substance Materials for Elementary School - Fauziah, Nurul; Ningsyih, Suriya (Asian Journal of Science Education, 2022)
The rapid flow of globalization has resulted in the erosion of local cultural values in Indonesia. This has resulted in a shift in content and neglected local wisdom. This study aims to produce and find the quality of thematic student worksheet-based ethnoscience on Single Substance and Mixed Substance Materials for Elementary Schools. This research is research and development (RD), with the development of the Nieveen model with preliminary stages, prototyping stages, summative evaluation, and systematic reflection and documentation. The subjects of this research are media expert validators and material expert validators, one elementary school teacher, and 10 students. The quality of the learning tools developed is measured through the analysis of validity and practicality. The product validity assessment uses a validation questionnaire distributed to experts, and the data obtained is analyzed using the feasibility percentage formula. The practicality of using a response questionnaire assessed by the teacher and students was analyzed using the percentage of practicality. This study resulted in average feasibility of 88.21% categorized as very feasible. The percentage of the practicality of each aspect is 94.33% and 93.33%, categorized as very practical. It was concluded that the LKPD developed met the criteria for developing quality products that were valid and practical. Based on this, it can be concluded that the product developed is feasible and practical to be applied in learning.